PERSONALITY DEVELOPMENT THROUGH INNATE TRAITS AND ENVIRONMENT IN ISLAMIC PSYCHOLOGY - Rismanto, Firman (Universitas prof. Dr. Moestopo (Beragama), 2024)
This study examines the impact of innate (nature) and environmental (nurture) factors on human psychological development, using the Quran and Hadith as foundational perspectives. The research employs a literature review, collecting data from books, journals, and other sources. The process involves identifying the main topic, using keywords to search academic databases, selecting quality literature, analyzing findings, and compiling results. The study reveals that while Allah SWT has meticulously designed human nature, individuals are shaped by genetic and environmental influences. Parents or caregivers significantly affect personality, behavior, and beliefs. The Quran and Hadith emphasize recognizing one’s nature, practicing gratitude, and following Allah's teachings to maintain faith and knowledge. Ultimately, humans are entrusted with the responsibility to fulfill their purpose in seeking Allah’s pleasure through worship and righteous living. Therefore, awareness of nature, knowledge, and practices in accordance with His teachings are fundamental to achieving the life purpose desired by Allah SWT.